Application of stable carbon and hydrogen isotope technology in the determination of gas sources from limestone layers at Shuangliu mine, China. (19th April 2021) - Zhou, Wei; Xue, Sheng; Han, Yunchun; Zheng, Chunshan
Abstract: Stable carbon and hydrogen isotope technology is used in determining gas sources in coal mines. Coal measures at the Shuangliu mine mainly contain nine coal seams (i.e. No. 2 to No. 10) and five limestone layers (namely, L1 to L5). The coal seams are interbedded with the limestone layers. A large amount of methane is adsorbed in the limestone layer, and the actual measured maximum gas pressure is 1.3 MPa, posing a serious gas emission safety risk in roadway excavation in the coal measures. In order to effectively manage the safety risk of gas emissions, it is necessary to determine gas sources and take necessary control measures. In this study, 50 gas samples were taken from the coal seams and 10 gas samples were collected from the limestone layers. These samples were measured for their composition and stable carbon and hydrogen isotopes. Stable carbon and hydrogen isotope tracer separation technique and multi-source linear calculation methods were used to analyze the measurement results. The study shows that 84% of gas in the L1, L2 and L3 limestone layers comes from the No. 8 coal seam and 11% from the No. 9 coal seam; gas in the L4 limestone layer is mainly from the No. 8 (44%), No. 7 (37%) and No. 6 coal seams (16%), and gas in L5 limestone layer mainly comes from the No. 6 (59%), No. 7 (23%) and No. 8 coal seams (13%). The research results can guide the design of gas drainage boreholes before roadway tunneling, so it has important guiding significance in the formulation of comprehensive gas control schemes.